Non-catastrophic Deep Cerebral Vein Thrombosis in COVID-19: case report: English (Ictus, 2021)
AbstractSARS-CoV-2 infection responsible for COVID-19, has demonstrated neurotropic and neuroinvasive potential, displaying several neurological manifestations ranging from mild to severe complications, the latter related to a prothrombotic state, giving place to stroke and less often cerebral venous thrombosis. The physiopathology of these events is currently elucidated from various mechanisms including thrombo-inflammation, endotheliopathy, and stasis in critically ill patients.Cerebral venous thrombosis is a possible complication of COVID-19 in any stage, even in patients with a non-severe course of the disease; the mechanism involved is probably related to microcirculatory dysfunction enhanced by prothrombotic comorbid conditions.
Keywords: COVID-19; Headache; Intracranial Sinus Thromboses; Stroke; SARS-CoV-2